Reign-seeking and the Rise of the Unelected in Thailand. Issue 3 (2nd July 2016) - Kanchoochat, Veerayooth
ABSTRACT: This article develops the concept of "reign-seeking" to capture the unprecedented collective action of the Thai professional and official elite prior to the 2014 military coup and the establishment of a military regime. It argues that this phenomenon reflects broad and deep political dynamics, for which the dominant scholarship on authoritarianism and Thai politics cannot adequately explain. The changing incentives of these supposedly non-partisan actors are interwoven with neo-liberal governance reform driven by a desire for depoliticisation and the minimisation of rent-seeking. This idea has been rationalised in Thailand since the promulgation of the 1997 Constitution resulting in the rise of technocratic and judicial bodies designed to discipline elected politicians and political parties. However, such institutional reconfigurations have consolidated the incentive for people considering themselves to be prospective candidates to "reign" in these organisations. As evident in the 2014 coup, these unconventional political actors – academics, doctors and civil society leaders – made collective efforts to topple the elected government in exchange for gaining selection into the wide range of unelected bodies. Governance reform in Thailand has hitherto reinforced the status quo, although the article further argues that reign-seekers should be seen as contingent, rather than consistent, authoritarians.